A field investigation into the mechanisms of pile ageing in sand. Issue 2 (18th February 2021) - Gavin, Kenneth; Igoe, David
Abstract : The design of axially loaded piles has been an area of focus for the offshore industry in recent years. A number of studies report substantial increases in the shaft capacity of piles driven in sand, known as pile ageing. The offshore industry has been slow to implement ageing into practice because of uncertainty over the mechanisms controlling ageing and variability on the impact of ageing. This paper presents the results of tests using an instrumented pile with two separate installations considered, one where the pile was load tested 4 days after installation and the second where the load test was performed after an ageing period of 116 days. Data from the installation, ageing period, load testing and pile extraction provide further insights into the mechanisms governing the effect of time on the axial capacity of piles in sand.